Draft Genome Sequence of the Virulent Avibacterium paragallinarum Serotype A Strain JF4211 and Identification of Two Toxins - Aguilar-Bultet, Lisandra (American Society for Microbiology, 2013)
Avibacterium paragallinarum is an important pathogen of chicken livestock causing infectious coryza. Here, we report the draft genome sequence of the virulent A. paragallinarum serotype A strain JF4211 (2.8 Mbp and G+C content of 41%) and the two toxin operons discovered from the annotation of the genome.